The Effect of Customer Satisfaction, E-Word of Mouth, and Initial Trust on Livin's Mobile Banking Adoption Interest - Komara, Edi; Tri Utami, Dina (Jurnal Manajemen, 2024)
This research aims to investigate the impact of positive Electronic Word of Mouth (eWOM) on the adoption of Mobile Banking. In this study, it was found that Argument Quality, Valence, and Customer Satisfaction have a positive influence on Initial Trust, which in turn affects the intention to adopt Mobile Banking. This study uses a descriptive research design approach with empirical data collected through an online survey of PT Bank X's customer respondents in East Jakarta. The collected data was subsequently analyzed using the Partial Least Square (PLS) analysis method with the aid of smartPLS 4.0 software. The results of this study, there is no positive impact from Consistency and Volume Review on Initial Trust. The findings of this study provide recommendations to banks to leverage positive eWOM to encourage customers to adopt Mobile Banking. These findings emphasize the importance of Customer Satisfaction in enhancing Initial Trust, which contributes to the usage of Mobile Banking applications and Customer Satisfaction